Strategi Komunikasi Guru Al-Islam Kemuhammadiyahan dalam Membina Akhlak Siswa di SMK Muhammadiyah Pangkalan Balai Kelas X Teknik Komputer Jaringan - Choky Parian; Ahmad Jumhan; Idmar Wijaya (CV. Jalan Cendikia, 2025)
During the caliphate period, communication facilities such as postal networks, letters, and messengers were developed to facilitate communication between the government and the public. In addition, mosques also served as communication facilities themselves, as they were places where people gathered to worship, learn, and share information. The objectives of this study are to analyze the factors underlying the communication strategies employed by Al-Islam and Kemuhammadiyahan teachers in nurturing and influencing the moral character of students at SMK Muhammadiyah Pangkalan Balai; and to analyze how Al-Islam and Kemuhammadiyahan teachers use communication strategies to nurture and influence the moral character of students at SMK Muhammadiyah Pangkalan Balai. This research is a qualitative case study, and data collection was conducted through interviews, observations, and documentation. Students in the 10th grade Computer Network Engineering class at SMK Muhammadiyah Pangkalan Balai and Al-Islam Kemuhammadiyahan teachers were the subjects of this research. The research findings indicate that: (1) the teachers' communication strategies emerged due to the need to create an open and adaptive learning environment suited to the diverse characteristics of students, as well as the importance of communication in effectively conveying Islamic moral values; (2) the communication strategies implemented include interpersonal communication, open discussions, persuasive approaches, the use of visual media, and the teachers' exemplary behavior reflecting Muhammadiyah values; (3) the challenges faced by teachers include the negative influence of social media, students' lack of understanding of the meaning of guidance, and students' psychological and emotional barriers. Teachers address these challenges by building empathetic communication, personal approaches, and continuous guidance.